Review of the Monograph «Biology of Diffuse Endocrine Epithelial System» Written by V. V. Yahlov, I. A. Mikhailyuk, N. V. Yahlova (Ivano-Frankivsk: Symfoniya forte, 2013. – 166 p.) - Lutsyk А.; Yashchenko A. (Львівський клінічний вісник)
Introduction. Monograph «Biology of Diffuse Endocrine Epithelial System», written by V. V. Yahlov, I. A. Mikhailyuk, N. V. Yahlova considers the structure and functioning of the diffuse endocrine system, which is an important component of the endocrine system of humans and animals, and is represented by the single receptor-endocrine cells located in the epithelium of the mucous membranes of the organs of the digestive, respiratory, genitourinary systems, and also in the skin. Aim. To make a review on monograph of V. V. Yahlov, I. A. Mikhailuk, N. V. Yahlova “Biology of Diffuse Endocrine Epithelial System”. Materials and methods. The rewiev of the monograph of V. V. Yahlov, I. A. Mikhailuk, N. V. Yahlova “Biology of the Diffuse Endocrine Epithelial System” was made. A detailed analysis of work by the sections was conducted, a professional evaluation of the results of many years of scientific research of authors was given, as well as formulated their own views on the prospects for further research in this field.